Microsoft Office 2007 - Hunt, Marjorie (Thomson Course Technology, 2008)
This Microsoft Office 2007 Illustrated Series book will appeal to all the learners in your classroom, from the computer rookies to the computer hotshots. It covers the essential information that you need to know about how to use Microsoft Office 2007. Our signature two-page spread design has been updated and refreshed to take full advantage of the new features of the Office 2007 software. This practical, easy to navigate book provides you with the essential knowledge you need to succeed at both work and beyond